Forecasting functional implications of global changes in riparian plant communities. Issue 8 (26th August 2013) - Kominoski, John S; Shah, Jennifer J Follstad; Canhoto, Cristina; Fischer, Dylan G; Giling, Darren P; González, Eduardo; Griffiths, Natalie A; Larrañaga, Aitor; LeRoy, Carri J; Mineau, Madeleine M; McElarney, Yvonne R; Shirley, Susan M; et al.
Abstract : Riparian ecosystems support mosaics of terrestrial and aquatic plant species that enhance regional biodiversity and provide important ecosystem services to humans. Species composition and the distribution of functional traits – traits that define species in terms of their ecological roles – within riparian plant communities are rapidly changing in response to various global change drivers. Here, we present a conceptual framework illustrating how changes in dependent wildlife communities and ecosystem processes can be predicted by examining shifts in riparian plant functional trait diversity and redundancy (overlap). Three widespread examples of altered riparian plant composition are: shifts in the dominance of deciduous and coniferous species; increases in drought‐tolerant species; and the increasing global distribution of plantation and crop species. Changes in the diversity and distribution of critical plant functional traits influence terrestrial and aquatic food webs, organic matter production and processing, nutrient cycling, water quality, and water availability. Effective conservation efforts and riparian ecosystems management require matching of plant functional trait diversity and redundancy with tolerance to environmental changes in all biomes.